2023
DOI: 10.1002/pbc.30774
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 is a key component of hepatoblastoma tumor cell growth

Kathryn Glaser,
Emily J. Schepers,
Harrison M. Zwolshen
et al.

Abstract: BackgroundEnhancer of zeste homolog 2 (EZH2) catalyzes the trimethylation of histone H3 at lysine 27 via the polycomb recessive complex 2 (PRC2) and plays a time‐specific role in normal fetal liver development. EZH2 is overexpressed in hepatoblastoma (HB), an embryonal tumor. EZH2 can also promote tumorigenesis via a noncanonical, PRC2‐independent mechanism via proto‐oncogenic, direct protein interaction, including β‐catenin. We hypothesize that the pathological activation of EZH2 contributes to HB propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Proto-oncogenes transform normal cells into functional oncogenes in four ways: acquisition of strong promoters and enhancers, chromosomal translocations, gene amplification, and point mutations, all of which are inseparable from the regulation of chromatin modifiers. For example, crosstalk between histone-modifying enzymes and enhancers promotes the activation of proto-oncogenes, causing tumors such as liver, breast, and colorectal cancers [89][90][91][92]. The G protein-coupled receptor A2A activates the proto-oncogene MYC to promote proline synthesis, and the increased level of proline metabolism recruits histone acetylases SIRT6 and SIRT7 to mediate the level of H3 deacetylation in prostate cancer cells, triggering the transformation of prostate adenocarcinoma into a neuroendocrine tumor [93].…”
Section: Cancermentioning
confidence: 99%
“…Proto-oncogenes transform normal cells into functional oncogenes in four ways: acquisition of strong promoters and enhancers, chromosomal translocations, gene amplification, and point mutations, all of which are inseparable from the regulation of chromatin modifiers. For example, crosstalk between histone-modifying enzymes and enhancers promotes the activation of proto-oncogenes, causing tumors such as liver, breast, and colorectal cancers [89][90][91][92]. The G protein-coupled receptor A2A activates the proto-oncogene MYC to promote proline synthesis, and the increased level of proline metabolism recruits histone acetylases SIRT6 and SIRT7 to mediate the level of H3 deacetylation in prostate cancer cells, triggering the transformation of prostate adenocarcinoma into a neuroendocrine tumor [93].…”
Section: Cancermentioning
confidence: 99%
“…Another model of HB PDOs was established by Glaser and colleagues, who used cells isolated from PDXs, to study the relationship between EXH2 and canonical Wnt signaling. In particular they silenced EZH2 genes by siRNA and reported that HB control cells form organoid while treated cells showed reduced cell aggregation into organoids, indicating as EZH2 inhibition have a potential role in HB pathogenesis ( 88 ). There is also another study that similar to the previously used HB organoids to test antitumoral efficacy in HB.…”
Section: Modeling the Solid-pediatric Tumors: Organoids As Tool To Un...mentioning
confidence: 99%